Congenital heart malformation in Yunis-Varón syndrome. Issue 9 (September 1993) - Adès, L C; Morris, L L; Richardson, M; Pearson, C; Haan, E A
Abstract : We describe a male infant with Yunis-Varón syndrome who has tetralogy of Fallot. This appears to be the first case of Yunis-Varón syndrome associated with congenital heart malformation.